Porous glasses with sodium nitrite impregnations - Rysiakiewicz-Pasek, Ewa; Poprawski, Ryszard; Urbanowicz, Adam; Mączka, Mirosław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
The properties of sodium nitrite introduced in porous glasses have been investigated. SEM graphs indicate existence of sodium nitrite inside glass pores. It has been shown that FTIR and Raman spectra are similar for bulk sodium nitrite and sodium nitrite embedded into porous glass. The nature of FTIR and Raman bands has been determined. The size-effect of sodium nitride introduced into porous glass was observed on the basis of dielectric measurements.
Optica Applicata, Vol. 35, 2005, nr 4, s. 769-774
Keywords: optyka; porous glass; ferroelectric; Raman spectra; FTIR